INTEGRASI PAYMENT GATEWAY DENGAN SISTEM IMIGRASI DI INDONESIA: TANTANGAN HUKUM DAN IMPLIKASI REGULASI DI ERA DIGITAL - Hamdi, Muhammad Arief; Wicaksono, Anggi; Hoesein, Zainal Arifin (Polteknik Imigrasi, 2024)
The development of digital technology has brought significant changes to various aspects of life, including payment systems and immigration. Payment gateway, as a critical innovation in the digital financial sector, enables fast and cross-border transactions. However, this progress also presents new challenges for the legal system, particularly in monitoring cross-border transactions that may be subject to misuse. This research focuses on the integration of payment gateways with the immigration system in Indonesia and the legal challenges that arise from this process. Using a qualitative approach, this study analyzes existing regulations in Indonesia, comparing them with other countries such as the United States, the European Union, and Singapore, and identifies areas that need improvement. The findings indicate that while Indonesia has a solid legal foundation, there is a need to strengthen regulations related to Anti-Money Laundering (AML), Know Your Customer (KYC), and data protection. The research also provides policy recommendations to enhance cross-agency collaboration between immigration authorities and fintech service providers to create a safer and more effective system for monitoring cross-border digital transactions.